SOL parallel momentum loss in ASDEX Upgrade and comparison with SOLPS. (August 2017) - Paradela Pérez, I.; Scarabosio, A.; Groth, M.; Wischmeier, M.; Reimold, F.; Upgrade Team, ASDEX
Highlights: In AUG experiments, strong electron pressure losses for T e, t < 10 eV and in the near SOL only) ⇒ f m o m = f m o m ( T e, t, ρ ) In SOLPS, f mom quantitatively weaker than in experiments and simple model. Apparent "momentum gain" explained by lack of ion channel measurements. In SOLPS, CX reduces flows in near SOL and PFR. Apparently, EL plays a very little role. Abstract: An H-mode database of ASDEX Upgrade plasmas with improved diagnostics for a variety of different plasma conditions has been analysed to study the momentum removal in the Scrape-Off Layer (SOL). A strong reduction, up to a factor of 100, of the electron pressure is observed close to the separatrix. Sets of L-mode and H-mode like plasma simulations with the SOLPS5.0 code package have supported the interpretation of the experimental observations (e.g., apparent momentum gain, strong radial position dependence) and helped to clarify the role of ion-neutral interactions. The experimental data are in turn used to check the SOLPS predictions, which differ quantitatively, suggesting that important pieces of physics are still not successfully captured by the code.